Modeling and Tuning of Speed Regulators for FPSOs Generation Systems - De Santana, Marcelo Patrício; Morales Paredes, Helmo Kelis [UNESP]; Serrão Gonçalves, Flávio A. [UNESP]; Paes, Felipe Leite; Liberado, Eduardo Verri [UNESP]; Geraldi, Edson Luis; Oliveira, Felipe Silva; De Moraes Pereira Da Rosa, Rodrigo; Marafão, Fernando Pinhabel [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
This paper presents the modeling and simulation of a gas-turbine-based power generation system used in offshore oil and gas (O&G) production platforms. The generation system consists of a synchronous generator, gas turbine, and voltage regulator. To ensure proper operation of the platform's generation system, it is crucial to design an effective speed regulator that can handle adverse operating conditions, such as load increases and load rejections. In this study, a technique similar to Virtual Reference Feedback Tuning (VRFT) and another with a genetic algorithm (GA) structure are employed to adjust the gains of the secondary controller of the speed regulator based on real measurement data. The generation system is simulated using the Matlab/Artemis/Simulink platform, and the results show transient frequency responses that resemble those of a real generation system under load increase and load rejection conditions.
Keywords: Gas-turbine Power Generation; Off-shore O&G Production Platform; Simulink; Speed regulator